Zastosowanie kasy fiskalnej jako narzędzia optymalizującego koszty sprzedaży w handlu detalicznym - Wyszkowska, Zofia; Krupa, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this work was to get know the function of cash registers and to define the optimum of hours when shops are open and optimal number of workers. The shop assistants files where the time of work is registered and printouts from checkouts that register the customer's movement were used. Information from 14 grocery stores were analysed. The analysis of data showed that the files and analysis of customer's movement lets make optimum of cost of selling and gives right customer service. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 438-446